Diversidade de mosquitos (Diptera: Culicidae) no bioma caatinga - Andrade, David Campos (2018)
The insects from Culicidae family have been widely studied since the last century due to their hematophagous habit, what turns some species into vectors of diseases. There are some biomes in which only a few studies about mosquitoes diversity can be found. One of them is Caatinga, a Brazilian biome characterized for high hydric deficit along the year. This study is divided into two chapters, the first aimed to gather existing inventories with the objective of checking mosquito species adapted to environmental restrictions imposed by Caatinga, analyzing the composition and distribution of species among communities. The second chapter is the description of a species from the genre Toxorhynchites Theobald 1901, subgenre Lynchiella Lahille 1904 which was found during the accomplishment of the project "Mosquitos de Caatinga". The surveillance gathered information about inventories held in Caatinga areas of for Brazilian states, between 2008 and 2014 years in the following areas: Estação Ecológica Raso da Catarina (EERC) in Bahia, Monumento Natural Grota do Angico (MNGA) in Sergipe; the North of Minas Gerais state (NMG); Floresta Nacional do Açu (FNA), Estação Ecológica de Seridó (EES) and a particular area known as Sítio Areias (SA). The three latter areas belong to Rio Grande do Norte state. Several collection techniques were carried out, including the collection of eggs, larvae, and adult individuals. It was utilized the partitioning of β diversity and its turnover indexes (βJTU) and/or nestedness (βJNE) in order to verify dissimilarities among communities. 81 species belonging to 14 genres were registered in Caatinga. The higher richness come from NMG (S=49) and MNGA (S=30) areas. The other areas have shown lower numbers in richness: 26 for EERC, 17 for FNA and 11 for EES. 35 species are shared among the areas, other 46 own exclusive occurrences. The areas owning the highest numbers of exclusive species were NMG, with 30%, also MNGA and EERC with 11% for each. The communities showed high rates of variation (βJAC =0.88), and the replacement mechanism is the main one framed up by the found pattern (βJTU =0.79, βJNE =0.09). This result may relate to the wide environmental heterogeneity of the Biome and to the ecological interactions of some species with their specific breedings. The species with higher distributions belong to the genres: Aedes, Anopheles, Psorophora, Haemagogus, Coquillettidiae e Mansonia, which are also of medical interest. The species described in the second chapter was found in EERC, Bahia. The species is a phytotelm-breeding species, taking bromeliads as a habitat. It was classified as belonging to a complex of species named Violaceus, morphologically closer to Tx. mariae species. The sub-genre of this species will now consist of 17 cataloged species.